Efecto de preparación mulch y abonamiento en el cultivo de la yuca (Manihot esculenta Crantz) en suelos arenosos de Colombia - Cadavid López, Luis Fernando; Acosta, Alvaro; El-Sharkawy, Mabrouk A. (1995)
Although cassava -a tropical crop- is regarded as a staple food crop for millions of people worldwide, it is still considered as a subsistence crop and seldom receives adequate crop management. Average yields are less than 8 t/ha. Colombia`s North Coast, where large areas of sandy soils are planted to cassava, is no exception. To study the effect of tillage, fertilizers, and surface applications of grass mulch on crop yields and on soil fertility, a trial was established in Pivijay, Magdalena. No significant differences were observed among tillage systems, although average yields were higher with tillage than without. Mulching had a marked beneficial effect, especially in unfertilized plots (15.5 versus 7.6 t/ha). Without mulching, and regardless of tillage, cassava`s response to fertilization was highly significant. The soil was also favored by Mulching: the levels of nutrients -N, P, K, Ca, and Mg- increased.